Quantitative Insights into Workplace Dynamics: Structural Equation Modeling of Multinational Corporations in Dubai - Abuhantash, Amer (International Review of Management and Marketing, 2025)
The study examines workplace dynamics in multinational corporations (MNCs) in Dubai through the application of Structural Equation Modeling (SEM). It explores key factors influencing employee satisfaction, productivity, and organizational commitment. Using a quantitative approach, survey data from employees of leading MNCs in Dubai were analyzed to identify latent variables and their interrelationships. The findings reveal that leadership style, cultural diversity, job satisfaction, and workplace environment significantly impact employee performance. This research provides empirical insights into HR strategies and corporate policies for enhancing workplace efficiency in a globally diverse business hub.